Rádio-educação : uma proposta diferenciada de suporte de texto para a educação de alunos com necessidades educativas especiais - Roos, Roberta (2007)
Most of schools ignore the insertion of new technologies in education. The reasons of this distance between education and technology are, among others, the lack of pedagogical tools due to the low economical conditions of most public schools, the lack of ability or even the lack of sensibility from most part of the teaching staff to identify the differences between the students and the way they are influenced on learning. There are different ways of teaching, because there are also different persons with different capacities but with the same right to learn. Under this reality, pedagogical alternatives are been ignored, damaging the development of the students with learning troubles. In this perspective, this research shows the radio as a simple and cheap alternative to the introduction of new technologies inside the schools. The radio is a popular mass medium at everybody s reach, by its low costs and easy understanding. The research counted on the introduction of three radio programs, where there was a writing and reading teaching review for a ten special students class. After the introduction, there were activities where verbal and body expressions, attention level and textual comprehension through the analysis of inferences and original text propositions were observed. This research process suggests, up against the high level of attention, the comprehension of text evidenced by the inferences fulfillment and production of original propositions, and the enthusiasm on the development of the activities of most students, that the radio can be used as a alternative text support on the writing and reading teaching process of students with mental deficiency and learning troubles